Money, Wages and Inflation in Middle-Income Developing Countries - Agenor, Pierre-Richard (IMF Working Papers; Working Paper, 1997)
This paper examines the short-run links between money growth, exchange rate depreciation, nominal wage growth, the output gap, and inflation in Chile, Korea, Mexico, and Turkey, using a generalized vector autoregression analysis. Nominal historical wage shocks are shown to have an important effect on movements in inflation only in Mexico. Generalized impulse response functions show that a positive historical shock to nominal wage growth generates a transitory but significant reduction in output. Inflation increases in all countries, particularly Mexico. A positive shock to nominal money growth raises real cash balances on impact and exerts an expansionary effect on output, despite an increase in real wages.